Al-Tarbiyah Al-Syahshiyah fi Indonesia (Diraasah min Al-Ithaar Al-Falsafi, wa Al-Qaanuun, wa Al-Tanfiidz, wa Al-Isykaaliyaat) - Widodo, Sembodo Ardi (Al-Ulum, 2015)
This article aims to describe the phenomena of character education in Indonesia. The study covers aspects of the philosophical outline about the importance of character education, the rudiments of law used as the basis, the implementation of character education at schools, and problems appeared in the field. Many cases such as corruption, juvenile delinquency, drugs miss-use, social conflict, and environmental damage occurred in Indonesia are among important factors of the implementation of character education. In this case, the government already set up the 18 character values that implanted through education, namely religiousness, honesty, tolerance, discipline, hard working, creativity, independence, democracy, curiosity, nationalism, patriotism, achievement, friendship and communication, peace-loving, reading, environmental care, social care, and accountability. Nonetheless, there are still many obstacles in the implementation of character education in the field. Those problems are analyzed comprehensively in this paper.Â -----Artikel ini dimaksudkan untuk menggambarkan fenomena pendidikan karakter di Indonesia. Kajian mencakup aspek kerangka filosofis tentang pentingnya pendidikan karakter, dasar-dasar hukum yang dijadikan landansan, implementasi pendidikan karakter di sekolah, dan problem-problem yang muncul di lapangan. Banyaknya kasus korupsi, kenakalan remaja, narkoba, konflik sosial, dan kerusakan lingkungan yang terjadi di Indonesia menjadi faktor yang penting diterapkannya pendidikan karakter. Dalam hal ini, pemerintah sudah menetapkan 18 nilai-nilai karakter yang ditanamkan melalui pendidikan, yaitureligius, jujur, toleransi, disiplin, kerja keras, kreatif, mandiri, demokratis, rasa ingin tahu, semangat kebangsaan, cinta tanah air, menghargai prestasi, bersahabat/komunikatif, cinta damai, gemar membaca, peduli lingkungan, peduli sosial, dan tanggung jawab. Namun demikian dalam realitasnya masih banyak dijumpai kendala dalam implementasinya di lapangan. Permasalahan-permasalahan inilah yang perlu dianalisis secara lebih mendalam dalam tulisan ini.